Factors Determining Interest Rate Derivatives Usage for Hedging In the UK - CHEN, JunChao (2010)
This study provides empirical evidence on the determinants of using derivatives for non-financial firms in the UK. Particularly, the study add a new variable (the proportion of outside directors minus inside directors) to help identify what on earth affects the decision and the extent of using interest rate derivatives, maximisation of shareholder value or maximisation of managerial utility. The data of off-balance-sheet instruments is obtained from 2009 annual reports of 230 firms which are listed in the FTSE 350. In final sample, there are 157 interest rate derivatives users and 73 interest rate derivatives non-users. The study applies the Logit model and OLS regression to examine the determinants of the decision to use interest rate derivatives and the determinants of the quantity of interest rate derivatives use respectively. Given the outputs of both analyses, the author concludes that the evidence on costs of financial distress hypothesis, contract costs hypothesis and substitutes for hedging hypothesis is mixed while the study provide evidence on taxes hypothesis. Moreover, the study suggests that the motive for using derivatives is maximisation of managerial utility.